Surface acoustic wave modes characteristics of CMOS compatible SiO2/AlN/SiO2/Si multilayer structure with embedded electrodes - Aslam, M.Z. (Elsevier B.V., 2020)
In this work, a CMOS compatible surface acoustic wave (SAW) device has been simulated and analyzed on SiO2/AlN/SiO2/Si. The simulation results have been used to characterize a typical fabricated device as well. The phase velocity, coupling coefficient, and temperature coefficient of frequency (TCF) of surface acoustic waves in the proposed structure have been investigated using the finite-element (FE) simulation. The simulation results show that a high velocity and a large effective coupling factor can be simultaneously obtained. Besides, the excellent nearly zero TCF is also achieved. The analysis further shows potential for designing high-frequency SAW devices that are CMOS compatible and temperature stable utilizing the Sezawa wave mode. Â© 2020 Elsevier B.V.